De-ashed-biochar slow-release N fertilizer increased NUE in alkaline calcareous soils under wheat and maize crops - Muhammad Rashid; Qaiser Hussain; Khalid Saifullah Khan; Sarosh Alvi; Shokat Ali Abro; Muhammad Akmal; Shahzada Sohail Ijaz; Muhammad Umer; Abdul Ahad Qureshi; Mohamed S. Elshikh; Humaira Rizwana; Muhammad Rizwan; et al. (Scientific Reports)
Abstract Recently biochar has widely been reported as carrier of SRFs. However, the performance of SRFs synthesized from pristine biochar is still low and could not achieve the significant benefits compared to conventional N fertilizers. To overcome this limitation and research gap, BSRFs were synthesized using modified / de-ashed biochar as N-carrier. We hypothesized that BSRFs would NUE especially in alkaline calcareous soils for whom there is no specific SRF exist previously. In this study, the efficacy of BSRF formulated with 1:1 mass ratio of de-ashed biochar and urea was compared with CU and CSRF for improving NUE under wheat (Triticum aestivum L.) and maize (Zea mays L.) cropping system in two different textured soils. The results showed that compared to CU and CSRF, the addition of BSRF significantly increased the retention of soil mineral-N (NH4 +-N, NO3 −-N) which, consequently, enhanced the crops’ N-uptake up to 23.71% in wheat and 26.55% in maize. It was further observed that SOC contents were increased up to 50.79% in wheat and up to 47.61% in maize at harvest. The addition of BSRF enhanced the CEC up to 32.95% under wheat and up to 27.73% under maize, compared to CU. Eventually, BSRF significantly increased the grain yield and NUE of wheat by 12.04% and 40.44%, while the maize grain yield and NUE increased by 21.06% and 45.56%, respectively. This study concludes that BSRFs had a stronger yield-increasing effect than CU alone attributing to enhanced N retention and crop uptake in alkaline calcareous soils. It was also found that the de-ashed biochar is a strong candidate to formulate new SRFs with improved performance.